Kontroversi Praktik Waris Adat Dalam Perspektif Moderasi Beragama - Yasin, Ahmad Alamuddin (Al-Mashlahah Jurnal Hukum Islam dan Pranata Sosial, 2022)
Some perceive that Islamic inheritance is considered insufficiently evenly distributed in division. Such as the division of boys is greater than that of girls. The issue is based on factors of individual needs in the family. The purpose of this study is to measure how much influence religious moderation has on the development of inheritance law in Indonesia. The author applies the method in this study with qualitative research methods by combining customary law and Islamic law in inheritance. The results of this study show that the application of customary inheritance in Indonesia carried out by Muslim communities is influenced by religion, culture and customs, as well as state law. This is influenced by the variety of Islamic patterns in Indonesia.